(untitled) (Research, Society and Development, 2021)
Self-medication is a worldwide phenomenon and its prevalence differs according to the population studied, the method and the recall period used. Therefore, the approach to the theme is necessary since it is a matter of concern for international authorities. A research was carried out in health databases, using inclusion and selection criteria for the selection of scientific articles. Then, the practice of self-medication was observed in individuals with higher schooling. Moreover, regarding the reason for self-medication, reports of previous experience in the treatment of recurrent symptoms were found, the perception of no severity in this action and no need for medical attention to treat the reported symptoms. The main classes of drugs observed were analgesics, anti-inflammatory drugs, antibiotics and drugs with action on the gastrointestinal system. Self-medication is a phenomenon with possible harmfulness and that must be fully understood and studied.